IMPLEMENTASI METODE HIWAR DALAM MENINGKATKAN KEMAMPUAN BERBICARA BAHASA ARAB SISWA DI SMP PLUS AL MAARIF BUNTET PESANTREN CIREBON - Alni Pebriani Awdiyanti; Ahmad Rifai; Sofandi (Al Naqdu, 2022)
Learn and understand language is very important for muslim mainly Arabic. Arabic is a half of religion. Basically, functions and roles of Arabic as brigde for identify islam by Al-Quran and Hadis. From the above presentation, the problem for this research is what are problems found by researchers who is teach Arabic at Junior High School Plus Al Maarif Buntet Pesantren Cirebon and solution taken by researchers to do learning Arabic at Junior High School Plus Al Maarif Buntet Pesantren Cirebon. To the know ploblem raise, researchers do reasearch use qualitative method with approach of ethnography and data collection technique include observations, interviews and documentations. From the research was found the cause of the lack of Arabic conversation refraction at Junior High School Plus Al Maarif Buntet Pesantren Cirebon among others are the lack of solidarity between teacher and students and the method taught by the teacher too monotone so it will become bore and lazy to take this subject. There is a solution in this problem can use hiwar method for expand students Arabic speaking skill.